Two new species of Elcaninae (Orthoptera, Elcanidae) recorded from the Early Cretaceous China - Tian, He; Ren, Dong; Gu, Jun-Jie (Zootaxa, 2022)
Two new species attributed to the genus Panorpidium Westwood, 1854 are described from the Lower Cretaceous Yixian Formation of Beipiao county, Liaoning province, China: Panorpidium acusicaudum sp. nov., P. validum sp. nov. The new species differs from all other known Panorpidium species by its combination of wing venation and body characters.